Analysis of Internal Conditions Improvement of Hutumuri Inpatient Community Health Center to Primary Class D Hospital in Ambon City; Feasibility Study of Hutumuri Inpatient Health Center - Bony Pattipawaey, Muhammad Alwy Arifin, Darmawansyah, Indar, Lalu Muhammad Saleh, Vonni Polopadang, Muhammad Kardi Rais, Muh. Yusri Abadi (International Journal of Advanced Science and Technology, 2020)
Responding to community demands for optimal health services, Hutumuri Community Health Center is trying to improve health services by developing a Primary D class hospital. In developing a hospital, a feasibility study is needed. The feasibility study was used to provide an assessment in the form of recommendations regarding the suitability of the Hutumuri Health Center to be upgraded to a Primary D class hospital. The purpose of this study was to conduct a feasibility study on the plan to increase the Hutumuri Public Health Center to become a Class D Primary Hospital in Ambon City. This type of research is quantitative with a case study approach. The subject of this research is data and information about internal conditions in improving the Puskesmas (Community Health Centyer) to become a Class D Primary hospital in the form of personnel/human resources, facilities and infrastructure, and types of health services. This study collected data through direct observation and secondary data processing (document review). The results showed that the internal factors of Hutumuri Community Health Center in terms of human resources and infrastructure were not yet feasible to be continued as a class D Pratama Hospital. Meanwhile, the health service aspect is feasible enough to be continued as a Class D Primary Hospital. To the Hutumuri Community Health Center, it is hoped that the existing workforce will improve both in terms of quantity and quality, as well as complete infrastructure according to the standard Regulation of the Minister of Health No. 24 of 2014.